2003
DOI: 10.1007/bf03041486
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection and sputum-culture conversion in patients diagnosed withMycobacterium tuberculosis: A population-based study

Abstract: Response to anti-tuberculosis therapy was significantly less favorable in HIV-infected than in HIV-uninfected tuberculosis patients. The importance of longer and closer monitoring of tuberculosis treatment in HIV-positive patients is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…HIV infection is also a widely described risk factor 7,8,14,15,16 , and our results showed it was associated with death and unsuccessful outcome. Studies have shown that improved TB outcomes can be achieved through decentralization of treatment and the supply of an extended range of supervised DOT options (even in countries where HAART is not readily available, like Malawi 25 ) and the integration of the DOTs strategy with HIV/AIDS homecare 25,26,27 .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…HIV infection is also a widely described risk factor 7,8,14,15,16 , and our results showed it was associated with death and unsuccessful outcome. Studies have shown that improved TB outcomes can be achieved through decentralization of treatment and the supply of an extended range of supervised DOT options (even in countries where HAART is not readily available, like Malawi 25 ) and the integration of the DOTs strategy with HIV/AIDS homecare 25,26,27 .…”
Section: Discussionmentioning
confidence: 50%
“…Some definitions consider only noncompliance, while others combine all negative outcomes: treatment failure, noncompliance, and death 4,5,6,7,8,9 . Determinants have included male gender 4,10 , older age 7 , migration 11 , homelessness 11,12,13 , history of incarceration 11,12 , alcoholism 12,13 , HIV infection 7,8,14,15,16 , intravenous drug use 12 , and decreased access to healthcare 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on chest x-ray examination, HIV infected patients presented more frequently with minimal cavitary disease when compared to HIV uninfected patients (p = 0.048). This has been previously described [13] and could be related to compromised immune responses induced by HIV infection [14]. All patients completed the full course of DOTS (Direct Observed Treatment Short Course).…”
Section: Resultsmentioning
confidence: 78%
“…15 In a study on HIV-infected people, only 33% of patients with smear-positive pulmonary tuberculosis were diagnosed in passive case finding; 16 it's worth mentioning that tuberculosis is the most common infection in people with HIV. 17 It was shown in a qualitative study that tuberculosis control program must pay more attention to some issues like co-incidence of TB and HIV, treatment-resistant tuberculosis, comprehensive education of society, providing services to patients with HIV/AIDS and treating the related infections. 18 It is also reported that lack of health insurance can cause patients not to refer to heath centers and thus can result in delay in diagnosing and finding new cases.…”
Section: Resultsmentioning
confidence: 99%